INNOVATIVE APPROACHES TO BUSINESS MODELING AT AN ENTERPRISE - Aleksandrovna Zavalko, Natalia; Olegovna Kozhina, Veronika; Vladimirovna Yudina, Elena; Nikolaevna Beketova, Olga; Valerievna Lavrenova, Alexandra (Revista Inclusiones, 2021)
The article is dedicated to the development of innovative approaches to business modeling at an enterprise. It has been established that the concept of forming a business model in the modern economic system is based on innovative dynamics and self-development. The practical importance of measures taken to elaborate the concept of a business model at an enterprise is related to the development of required and sufficient conditions for innovative self-development of regional systems, as well as the formulation of strategies for regional systems to adapt to features of economic and technologic realities.